11 Fatigue intervention co-design study: unique needs of teenagers and young adults with cancer-related fatigue. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Spathis, A; Chapman, A; Burkin, J; Hatcher, H; Uttenthal, B; Robson, J; Abbas, L; Gibson, F; Stone, P; Booth, S; Barclay, S
Abstract : Background: Fatigue is the most prevalent and distressing symptom experienced by teenage and young adult (TYA) cancer patients. It has a particularly negative impact at this young age, hindering key developmental needs such as independence. Despite this, there have been no interventional studies focused on its management in TYAs. Exercise, psychological techniques and energy conservation are the most effective approaches in older adults. TYAs, however, report finding current fatigue management strategies unhelpful. We therefore conducted a study, working with TYA patients and their parents, to co-design a fatigue intervention that better meets their needs. Methods: Thirteen patients aged 16–27 and within a year after the end of cancer treatment, and ten parents were recruited. In a three-phase iterative study design, participants took part in semi-structured interviews and focus groups. They then received the co-designed prototype intervention, before a final phase of feedback and amendment. Results: Participants described multiple age-related needs. Cognitive fatigue was more problematic than physical fatigue, and participants valued support explaining this to staff at education or work. Advice to exercise was most helpful when it included an individualised, structured plan, given the physical reserve of youth and fear that activity may worsen fatigue. The distress of fatigue was compounded by multi-level misunderstandings, particularly with parents, supporting parent inclusion in the intervention. Energy conservation and pacing were seen as irrelevant at this age, with a preference for App-based mindfulness techniques. Information was most acceptable in short video, rather than written, format. Conclusion: TYA cancer patients demonstrated unique needs from a fatigue intervention. Symptom control research findings involving older adults cannot necessarily be extrapolated to younger patients. The novel intervention co-design process was highly feasible and led to mutual benefit for participants and researchers. The effectiveness of the co-designed intervention now needs to be tested in a controlled trial.